2018
DOI: 10.3847/1538-4357/aac82d
|View full text |Cite|
|
Sign up to set email alerts
|

The Brightest Galaxies in the Dark Ages: Galaxies’ Dust Continuum Emission during the Reionization Era

Abstract: Though half of cosmic starlight is absorbed by dust and reradiated at long wavelengths (3µm-3 mm), constraints on the infrared through millimeter galaxy luminosity function (the 'IRLF') are poor in comparison to the rest-frame ultraviolet and optical galaxy luminosity function, particularly at z > ∼ 2.5. Here we present a backward evolution model for interpreting number counts, redshift distributions, and cross-band flux density correlations in the infrared and submillimeter sky, from 70µm-2 mm, using a model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
226
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(256 citation statements)
references
References 198 publications
(256 reference statements)
28
226
2
Order By: Relevance
“…Thus, to firstorder redshift evolution in the peak wavelength for massselected sources is consistent with the well-established L FIR -λ peak relation and redshift evolution in average farinfrared luminosity of galaxies selected at a fixed stellar mass (see Figure 9), and should not be interpreted in terms of a global λ peak (T dust )-z relation. Casey et al (2018b) recently presented a best-fit L FIRλ peak relation for a heterogeneous sample of far-infraredto-millimeter-selected galaxies at z = 0-6, which was subsequently employed in a phenomenological model of galaxy evolution designed to estimate the number counts and redshift distribution of sub-mm / mm sources (Casey et al 2018a). The L FIR -λ peak relation presented by Casey et al (2018b) lies systematically above our results by ∼ 5-10 µm, at a fixed far-infrared luminosity, with the offset increasing to ∼ 15-20 µm for the most luminous systems (see Figure 10; equivalent to ∆ T d ∼ 3-7 K).…”
Section: Redshift Evolution In the Average Sedmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, to firstorder redshift evolution in the peak wavelength for massselected sources is consistent with the well-established L FIR -λ peak relation and redshift evolution in average farinfrared luminosity of galaxies selected at a fixed stellar mass (see Figure 9), and should not be interpreted in terms of a global λ peak (T dust )-z relation. Casey et al (2018b) recently presented a best-fit L FIRλ peak relation for a heterogeneous sample of far-infraredto-millimeter-selected galaxies at z = 0-6, which was subsequently employed in a phenomenological model of galaxy evolution designed to estimate the number counts and redshift distribution of sub-mm / mm sources (Casey et al 2018a). The L FIR -λ peak relation presented by Casey et al (2018b) lies systematically above our results by ∼ 5-10 µm, at a fixed far-infrared luminosity, with the offset increasing to ∼ 15-20 µm for the most luminous systems (see Figure 10; equivalent to ∆ T d ∼ 3-7 K).…”
Section: Redshift Evolution In the Average Sedmentioning
confidence: 99%
“…Open symbols represent our stacking results for "active" galaxies in the COSMOS field at z < 1.5 that were selected based on the N U V -r and r-J colors. For comparison we show a sample of infrared-bright sources at z = 0-1 (Symeonidis et al 2013; typical uncertainty is shown in the lower left) and the best-fit relation to a heterogeneous sample of far-infrared-selected systems at z = 0-6 (Casey et al 2018b). We construct a simple model for the expected trend between λp and L FIR , which shown for galaxies at log 10 M = 10.0-10.5 (dot-dash), 10.5-11.0 (solid), and 11.0-12.0 (dashed).…”
Section: Redshift Evolution In the Average Sedmentioning
confidence: 99%
See 1 more Smart Citation
“…The LFs from Béthermin et al (2017) and Aoyama et al (2019) are shown in orange and light green, respectively. The results of the dust-poor model are shown in cyan and the dust-rich model in red Casey et al (2018). feedback. Dust is generated by supernovae and AGB stars and can grow by accretion.…”
Section: Comparison With Modelsmentioning
confidence: 99%
“…At z ≥ 6.8, the [O I] 63 shifts outside the Band 9, and is only redshifted into Band 8 at z ≥ 8.5, when the required on-source time increases into hours. In contrast to G09.83808-like sources, detecting the [O I] 63 emission from normal star-forming galaxies such as the population from the Olsen et al The modest expense of ALMA time required to detect the [O I] 63 emission from G09.83808-like DSFGs will allow an efficient follow-up of z 6 DSFGs which will be delivered by the on-going and planned mm-wave surveys (e.g., Casey et al 2018;Zavala et al 2018a;Magnelli et al 2019 line is in agreement with radiative transfer models of star-forming galaxies (e.g., Kaufman et al 1999Kaufman et al , 2006Narayanan & Krumholz 2017;Olsen et al 2017 145 observations are necessary to distinguish between the two scenarios.…”
Section: Detecting the [Oi] 63-um Emission From Zmentioning
confidence: 99%